1987
DOI: 10.1203/00006450-198704000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Rise of Prostanoids in Rat Small Intestinal Mucosa following Intestinal Protein Hypersensitivity

Abstract: ABSTRACI'. The purpose of the present study was to establish whether there is an elevated prostaglandin concentration in the intestinal mucosa in rats suffering from an immediate type hypersensitivity reaction. Rats of the Hooded-Lister strain were sensitized and challenged with ovalbumin. Control rats were given adjuvant only. Prostanoid content of scraped mucosa was determined by radioimmunoassay. It was found that the prostaglandin Ez content in the sensitized intestine was significantly elevated as compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The authors suggested that LTB 4 may be involved in the pathogenesis of the inflammatory process in IBD. In a rat model of ovalbumin protein hypersensitivity, we have demonstrated significantly elevated content of PGE z (20) and LTB 4 (21) in the small intestinal mucosa of ovalbumin-sensitized and challenged rats compared to controls.…”
Section: Resultsmentioning
confidence: 80%
“…The authors suggested that LTB 4 may be involved in the pathogenesis of the inflammatory process in IBD. In a rat model of ovalbumin protein hypersensitivity, we have demonstrated significantly elevated content of PGE z (20) and LTB 4 (21) in the small intestinal mucosa of ovalbumin-sensitized and challenged rats compared to controls.…”
Section: Resultsmentioning
confidence: 80%
“…, bowel hypoxia. Changes reaction , that there is an increase in the bowel content of PGE z and LTB 4 (23,24). In a study by Hyman et al (5) the levels of thromboxane B z were measured in the urine of infants with NEC, and found to be higher than in term healthy infants ; moreover, a gradual decrease in those levels paralleled clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of mucosal mast cells leads to release of a number of preformed and newly synthesized pharmacologically active mediators [5]. These include 5-hydroxytryptamine (5-HT), histamine and the arachidonic acid metabolites prostaglandin D 2 (PGD2) and prostaglandin E 2 (PGE2) which are capable of inducing active C1-secretion [6][7][8] and are known to be released during antigen stimulation of sensitized epithelial tissue [9,10]. In addition, it is known that stimulation of submucosal neurones results in C1-secretion and that 5-HT will activate enteric cholinergic neurones within the submucosal plexus [11].…”
Section: Introductionmentioning
confidence: 99%